Promoting fit Malaysia campaign / Shafiq Nazreen Nasfu - Nasfu, Shafiq Nazreen (2015)
The purpose of this research is to promote a campaign about Fit Malaysia. This campaign was directed by Kementerian Belia dan Sukan (KBS) which is the brainchild of Khairy Jamaluddin, the Malaysian Minister for Youth and Sports. Fit Malaysia aim to facilitate the adoption of healthy lifestyles amongst all Malaysia. It is also part of ministry aspiration to make Malaysia a true sporting nation and this campaign is a good idea from government as a springboard to cultivate sporting success on the global playfield. To understand about the promoting this campaign, it is important to know what type of promoting that related to this campaign. The main problem for this campaign is lack of advertisement or another word is advertising, for an example like poster, bunting, banner, magazine ads, newspaper and TV commercial. These things are very important because this method can promote the campaign to the public. Fit Malaysia aim to facilitate the adoption of healthy lifestyles amongst all Malaysia but the issue is this event only get support from people only who like to do sports and fitness activities while for those who do not like to active in this things, For sure this people will not join this event because they are not interested.At the end of this research, there have a suggestion and idea how to solve this problem and the important things that they should know what is necessary for a successful advertising campaign.